The analgesic potential of cannabinoids - Duarte, Célia (Journal of the Portuguese Society of Anesthesiology, 2016)
Cannabis as been used as an addict drug. Its consequences are not completely known (ex. dependence, schizophrenia, airway diseases and male infertility). The investigation around its therapeutic potential as began in the 90’s. The endocannabinoid system and specific receptors were discovered: CB1, CB2, TRP and atypical receptors. Animal and human investigation shows that synthetic cannabinoids may prove to become very useful in acute and chronic pain treatment.